1996
DOI: 10.1007/bf00191687
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and measurement of helicopter rotor flow with swept back tip shapes at hover flight using the “flow visualization gun” time line technique

Abstract: The Flow Visualization Gun (FVG), a novel time line visualization technique, has been used to investigate the flow field of a helicopter rotor with swept back tip shape in hover flight condition. After introducing the FVG-technique, the paper presents some visualization photographs of the rotor blade tip vortices and the rotor downwash. Using orthogonal sets of flow photographs and digital image analysis, the 3-dimensional time line displacement within the flow and the tip vortex structure are determined. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Numerical studies have focused on the main factors affecting the performance of propellers in various configurations [8][9][10][11][12][13][14] and models have been developed which allow the prediction of propeller aerodynamics at relatively low computational cost, in particular using time domain panel methods *Address correspondence to this author at the Dipartimento di Tecnologie ed Infrastrutture Aeronautiche, Università di Palermo, Italy; E-mail: romario@unipa.it [15,16] which allow for the inclusion of unsteadiness effects due to oscillation and blade deflection. Comparison with measurements on rotors in hover [17] have shown that quasisteady models give good results for unsteady aerodynamics. This justifies the use of hybrid methods using free wake analysis (FWA) and boundary element methods (BEM) for the aerodynamics of propellers [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical studies have focused on the main factors affecting the performance of propellers in various configurations [8][9][10][11][12][13][14] and models have been developed which allow the prediction of propeller aerodynamics at relatively low computational cost, in particular using time domain panel methods *Address correspondence to this author at the Dipartimento di Tecnologie ed Infrastrutture Aeronautiche, Università di Palermo, Italy; E-mail: romario@unipa.it [15,16] which allow for the inclusion of unsteadiness effects due to oscillation and blade deflection. Comparison with measurements on rotors in hover [17] have shown that quasisteady models give good results for unsteady aerodynamics. This justifies the use of hybrid methods using free wake analysis (FWA) and boundary element methods (BEM) for the aerodynamics of propellers [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…on the wake at the M nodes along the trailing edge. There, one has, via the trailing edge condition, i.e., Eq (17). and j are the potential values at the upper and lower trailing edge of the j-station taken along the blade radial sections distribution, respectively.…”
mentioning
confidence: 99%